Effect of Katuk Leaves (Sauropus androgynus (L.) Merr) on Breast Milk Production - Sri Handayani; Yopi Suryatim Pratiwi; Nurul Fatmawati (Universitas Islam Bandung, 2022)
Exclusive breastfeeding can reduce infant mortality in Indonesia. Lack of breastfeeding is one of the causes of the low achievement of exclusive breastfeeding. Sauropus androgynus (L.) Merr (katuk) leaves are believed to increase milk production. Most people process katuk leaves to make vegetable soup, while improper processing methods can reduce the beneficial effects. This study aimed to analyze the effect of katuk leaf soup consumption on breast milk production. The subjects in the study were postpartum mothers and their babies from October to November 2021 at the PONED Health Center in West Lombok regency who met the sample criteria. This research is a randomized controlled trial. The sample used is 32 respondents. Katuk clear soup was given to the intervention group and Asifit to the control group. The data collected was processed by a nonparametric test. The analysis showed no difference in katuk clear soup and Asifit on breast milk production (p=0.105). Therefore, breast milk production increased due to katuk clear soup and Asifit made from katuk leaves. This research concludes that katuk leaves are proven to increase breast milk production. Therefore, katuk leaf vegetables can be used as an effort to increase breast milk.